Closing the Knowledge-Application Gap in Organisations through Incentives: Experience from the National Water and Sewerage Corporation in Uganda. (October 2016) - Mvulirwenande, Silas; Alaerts, Guy; Wehn, Uta
Abstract: Recent decades have seen a steady rise of knowledge and capacity development (KCD) interventions targeting organisations in developing countries. This paper argues that very often the main challenge facing organisations is not the development of knowledge and capacity per se, but their actual use. Drawing on the case of Uganda's National Water and Sewerage Corporation (NWSC), we identify and discuss a number of interrelated factors (internal and external) that have allowed the utility to turn its knowledge base into improved performance. We conclude that utilities can close their knowledge-application gap by introducing a corporate culture that motivates staff to apply their knowledge. Highlights: Formal systems for capacity development are necessary, but not sufficient for improved performance. Organisational poor performance is often due to the weak application of already existing knowledge. Leadership, accountability, incentives and enabling environment are key drivers of knowledge application in water utilities. Water utilities can solve their knowledge management challenges by adapting what has worked well in other sectors. Changing corporate culture in public utilities is possible, provided that leaders are committed and use robust approaches.